Evaluation of Companies: Consistent Approaches - GRIBOV, Alexander Fedorovich; MAXIMOV, Denis Alekseevich; DOROKHINA, Elena Yuryevna (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The article discusses the problems of valuing companies. It is shown that on the basis of a generalized model in comparison with the Modigliani-Miller models a number of contradictions can be explained, arising in solving problems of evaluating the effectiveness of investment decisions. It is also shown that the formulas known in corporate finance sometimes lead to false judgments in cases of calculating the value of companies with a debt burden.